Significações de família por profissionais da proteção social básica: uma pesquisa em Unidade do CRAS do Sul do Maranhão - Macedo, Péricles de Souza (2023)
This master's thesis has as general objective to analyzemeanings of family by professionals of basic social protection. The research is theoretically and methodologicallyguidedbySocio-HistoricalPsychologyandisjustifiedbythescarcity of studies inthefieldof socialpsychologythat focusonthetheme,aswellasbythe centralityof thefamilyinsocial assistanceactions.Toachievetheoutlinedobjective, three interviewswereconductedwithworkersofaCRASintheinteriorofMaranhão, in the format of aconversationcircle.Methodologically, theanalysisusedNucleiof Meaning. Intheresults, themeaningofomittedfamilyappearsfrequently.Despitethe criticisms of the notion of structured family, this idea still persists andguides the practices of professionals who work in this field of social protection. Another phenomenonthat frequentlyappearsconcernsthecontradiction:difficultyofadherence of families to social assistance services versus lack of objective conditions that permeate thispolicy.Thephenomenonof social inequalityappearedasanimpassein the work developed with the families, not being recognized as centrality in the conditions facedbytheworkof theseprofessionals.Thedatapoint totheneedforan advance in the socio-assistance praxiswith regard toworkingwith families. It is understoodthatthemeaningsconstitutetheprofessionalpractices,infunctionofwhatis shown to be fundamental, for the qualification of this public policy, to point to possibilities of praxis that consider the real families that arriveat thedevices. The tensionbetweenaprotectiveperspectiveandafamilyperspectiveremains inpolitics andneedstoberecognizedinordertoproducenewsyntheses.